Immune Activation and Collateral Damage in AIDS Pathogenesis - Miedema, Frank; Tesselaar, Kiki; Baarle, Debbie; Borghans, Jose; Hazenberg, Mette; De Boer, Rob J. (Frontiers in Immunology, 2013)
In the past decade, evidence has accumulated that HIV-induced chronic immune activation drives progression to AIDS. Studies among different monkey species have shown that the difference between pathological and non-pathological infection is determined by the response of the immune system to the virus, rather than its cytopathicity. Here we review the current understanding of the various mechanisms driving chronic immune activation in HIV infection, the cell types involved, its effects on HIV-specific immunity, and how persistent inflammation may cause AIDS and the wide spectrum of non-AIDS related pathology. We argue that therapeutic relief of inflammation may be beneficial to delay HIV disease progression and to reduce non-AIDS related pathological side effects of HIV induced chronic immune stimulation.